2018
DOI: 10.1177/0194599818789146
|View full text |Cite
|
Sign up to set email alerts
|

Platelet‐Rich Plasma Fat Graft versus Cartilage Perichondrium for Repair of Medium‐Size Tympanic Membrane Perforations

Abstract: Objectives To compare clinical and audiologic outcomes among patients who underwent myringoplasty with fat graft enriched with platelet-rich plasma and cartilage perichondrium graft. Study Design Prospective randomized controlled study. Setting Department of Otolaryngology-Head and Neck Surgery, Tanta University, Egypt. Subjects and Methods The study comprised 50 patients who had tympanic membrane perforation of medium size (25%-50% of its surface area) without evidence of active otitis media or ossicular abno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
29
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(32 citation statements)
references
References 17 publications
3
29
0
Order By: Relevance
“…Multiple factors may affect the outcome of myringoplasty, like the age of the patient, site and size of the perforation, type of graft, surgical technique, experience of the surgeons, and condition of the ear whether it is dry or wet 2. Mandour et al,13 compared the use of the fat graft to the cartilage graft the reported success rates of 92% fat graft and 88% of cartilage graft. In our study, 2 important factors had an effect on the outcome of myringoplasty: the surgeon’s skills and expertise and the site of perforation.…”
Section: Discussionmentioning
confidence: 99%
“…Multiple factors may affect the outcome of myringoplasty, like the age of the patient, site and size of the perforation, type of graft, surgical technique, experience of the surgeons, and condition of the ear whether it is dry or wet 2. Mandour et al,13 compared the use of the fat graft to the cartilage graft the reported success rates of 92% fat graft and 88% of cartilage graft. In our study, 2 important factors had an effect on the outcome of myringoplasty: the surgeon’s skills and expertise and the site of perforation.…”
Section: Discussionmentioning
confidence: 99%
“…Of the 34 nonrepetitive studies identified, eight studies [8][9][10][11][12][13][14][15] including 455 participants with different sizes of TM perforations were eligible for final selection after screening the full texts. These included studies published from 2015 to July 2020 and consisted of five RCTs [9,10,[12][13][14], one prospective study [15], and two retrospective studies [8,11]. Seven of the included studies [8][9][10][12][13][14][15] compared the efficacy of PRP with conventional tympanoplasty or myringoplasty.…”
Section: Characteristics Of the Included Studiesmentioning
confidence: 99%
“…These included studies published from 2015 to July 2020 and consisted of five RCTs [9,10,[12][13][14], one prospective study [15], and two retrospective studies [8,11]. Seven of the included studies [8][9][10][12][13][14][15] compared the efficacy of PRP with conventional tympanoplasty or myringoplasty. Among the seven studies in which the experimental groups received PRP three involved fat graft myringoplasty (FGM) [8,9,14], one used conchal perichondrium myringoplasty (PM) [13], and three involved temporalis fascia tympanoplasty (TFT) [10,12,15].…”
Section: Characteristics Of the Included Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…In our second paper, Mandour and colleagues compare the clinical and audiometric outcomes of patients undergoing myringoplasty with adjuvant platelet-rich plasma fat grafts and those undergoing myringoplasty with cartilage-perichondrial graft. 2 Patients undergoing myringoplasty were randomly assigned to receive 1 of the 2 adjuvant techniques and were then evaluated on successful closure of the perforation and mean overall improvement in pure tone average on audiometry. In evaluating results of the 25 patients in each treatment group, the authors noted no significant differences in either audiologic outcomes or closure of perforation at 3 months postsurgery.…”
mentioning
confidence: 99%